Age associated decrease of sialin in salivary glands. (3rd October 2018) - Li, L; Wang, H; Hu, L; Wu, X; Zhao, B; Fan, Z; Zhang, C; Wang, J; Wang, S
Abstract: Aging salivary glands are characterized by a reduced volume of acini, increased duct volume, decline in the rate of synthesis of proteins and their mRNA, and decreased saliva flow. Sialin is a versatile anion transporter that is highly expressed in salivary glands and may also participate in maintenance of salivary gland function. We investigated age-associated sialin expression in salivary glands. Submandibular glands of mice and human parotid gland were collected at different ages. Western blot and real-time reverse transcription-polymerase chain reaction were used to analyze the protein and mRNA expression levels of sialin, respectively. Immunohistochemical and immunofluorescence staining were used to evaluate the histological pattern of sialin expression. We found that the protein and mRNA expression levels of sialin decreased with aging. The expression of sialin in the striated and excretory ducts of both mouse and human glands were reduced with age. In the mouse glands, the basal 2/3 of the cytoplasm was stained, while in the human glands the stain extended to the luminal surface. Sialin was expressed in the basal cytoplasmic membrane of acini and in some myoepithelial-like cells in young salivary glands, but had nearly disappeared in the aged salivary glands. Changes in sialin expression may be associated with changes in physiological function of salivary glands with aging.